STUDY ON TOURISM MANAGEMENT AND PROTECTION OF VOLCANOES NATIONAL PARK LANDSCAPE IN RWANDA - Faustin, Habumuremyi; Fuhua, Xuan (International Journal of Modern Hospitality and Tourism, 2021)
Purpose: National Park Landscape management approaches designed at governmental level do not necessarily represent the all-important stakeholder's involvements as consequence sustainable management and protection couldn't be achieved. The purpose the study was to investigate how selected stakeholders describe the current situation about the management and protection of VNPL, how they participate in tourism management and protection of VNPL, what perceived benefits from tourism and what it can be done to improve management and protection of VNPL. Methodology: Quantitative research methods have been used and purposive sampling technique has been applied whereby specific criteria to select respondents from local residents and local authorities in four districts of North-West province of Rwanda were considered. Findings: After analyzing collected data through closed and partial pre-coding questionnaires, the study found that there is lack of knowledge of residents about how they can involve in maintaining the sustainability of VNPL, lack of residents involvement in decision-making, less interaction opportunities between park's stakeholders and interest conflicts over resources between VNP stakeholders. Unique Contribution to Theory, Practice and Policy: The study suggests re-designing of VNPL management and protection policies, Increasing Tourism Investment and MSMEs in the region, Linking sustainable tourism and sustainable food systems, improving communication with local community and Adopting evidence-based rural tourism mechanism